Ivo Andrić and the culture of forgetting - Đurković Uroš Z. (Baština, 2022)
Ivo Andrić's literary work is analyzed in terms of the culture of forgetting. The culture of forgetting is comprehended neither as an antithesis of the culture of remembrance, nor as a political or ideological construct, but as a particular Andrić's sensibility, that shows the ubiquitous wish for being overwhelmed by non-existence, preserved in disappearance, fused with oblivion in silence. Therefore, certain aspects of Andrić's literary work in the light of the culture of forgetting are emphasized: 1) silence as a form of forgetting; 2) theatre stage and play as strategies of forgetting; 3) snow as an important motif in Andrić's literature. Special attention is given to the four of Andrić's short stories: The Bridge on the Žepa (Most na Žepi), Aska and the Wolf (Aska i vuk), Play (Igra), and Children (Deca).